The Isoenzymic Diketocamphane Monooxygenases of Pseudomonas putida ATCC 17453—An Episodic History and Still Mysterious after 60 Years - Willetts, Andrew (Microorganisms (Basel), 2021)
Researching the involvement of molecular oxygen in the degradation of the naturally occurring bicyclic terpene camphor has generated a six-decade history of fascinating monooxygenase biochemistry. While an extensive bibliography exists reporting the many varied studies on camphor 5-monooxygenase, the initiating enzyme of the relevant catabolic pathway in Pseudomonas putida ATCC 17453, the equivalent recorded history of the isoenzymic diketocamphane monooxygenases, the enzymes that facilitate the initial ring cleavage of the bicyclic terpene, is both less extensive and more enigmatic. First referred to as ‘ketolactonase—an enzyme for cyclic lactonization’—the enzyme now classified as 2,5-diketocamphane 1,2-monooxygenase (EC 1.14.14.108) holds a special place in the history of oxygen-dependent biochemistry, being the first biocatalyst confirmed to undertake a biooxygenation reaction equivalent to the peracid-catalysed Baeyer–Villiger chemical oxidation first reported in the late 19th century. However, following that auspicious beginning, the biochemistry of EC 1.14.14.108, and its isoenzymic partner 3,6-diketocamphane 1,6-monooxygenase (EC 1.14.14.155) was dogged for many years by the mistaken belief that the enzymes were true flavoproteins that function with a tightly-bound flavin cofactor in the active site. This misconception led to a number of erroneous interpretations of relevant experimental data. It is only in the last decade, initially as the result of pure serendipity, that these enzymes have been confirmed to be members of a relatively recently discovered class of oxygen-dependent enzymes, the flavin-dependent two-component monooxygenases. This has promoted a renaissance of interest in the enzymes, resulting in programmes of research that have significantly expanded current knowledge of both their mode of action and regulation in camphor-grown P. putida ATCC 17453. However, some features of the biochemistry of the isoenzymic diketocamphane monooxygenases remain currently unexplained. It is the episodic history of these enzymes and some of what remains unresolved that are the principal subjects of this review.